PENGETAHUAN, EDUKASI PHBS DAN DUKUNGAN KELUARGA BERHUBUNGAN DENGAN PERILAKU ORANG TUA DALAM MENCEGAH STUNTING - Azwar, Herlyssa; Sukmawati, Dewi; Sukamti, Sri; Safrudin, Safrudin (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Stunting is one of the health problems. According to WHO (2022), cases of stunting in toddlers under 5 years of age in the world are still quite high, namely 22.3%. The high number of stunting cases is partly triggered by the low behavior of parents in preventing stunting. This study aims to determine the relationship between PHBS education factors and parental behavior in preventing stunting. This study is a quantitative study with a cross-sectional design. The population and sample are parents who have children aged 0-5 years and visit the Pasar Rebo District Health Center as many as 132 respondents with a sampling technique in the form of purposive sampling. There is a significant relationship between the variables of knowledge, PHBS education and family support with parental behavior in preventing stunting. The results of this study show that parents who have good behavior are 65.2%. Most respondents have an age that is not at risk of 75.8%, are highly educated (91.7%), and are not working at 66.7%. have low knowledge about stunting of 47.7%, never been exposed to PHBS education of 43.2% and receive family support of 63.6%. There is a relationship between the variables of knowledge, PHBS education and family support with parental behavior in preventing stunting at the Pasar Rebo District Health Center. For this reason, efforts are needed to increase family knowledge about preventing stunting. Health workers continue to promote PHBS education and remind that family support is very important in preventing stunting in children aged 0-5 years. Keywords: Stunting; Behavior; Knowledge; PHBS Education; Family Support